TRANSFORMATION OF EDUCATIONAL FINANCING SYSTEMS THROUGH FINANCIAL MANAGEMENT DIGITALIZATION IN MADRASAH - Nurul Fitria; Subaidi Subaidi; Sukarman Sukarman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
The The advancement of digital technology has driven significant transformations in various aspects of educational management, including financing systems in madrasahs. The digitalization of financial management has become a strategic approach to promoting more effective, efficient, transparent, and accountable financial governance. This study aims to analyze the transformation of the educational financing system through the digitalization of financial management in madrasahs, as well as to examine its benefits, challenges, and implementation strategies. This study employed a library research method with a qualitative approach. Data were collected through documentation of scientific literature, books, journal articles, educational regulations, and relevant previous studies. Data analysis was conducted using content analysis to identify concepts, patterns, and findings related to the digitalization of educational financial management. The findings reveal that the transformation of the educational financing system in madrasahs has occurred across all stages of financial management, including planning, implementation, reporting, monitoring, and evaluation. The implementation of digitalization through various technology-based financial systems and applications has improved administrative efficiency, transaction recording accuracy, transparency in fund utilization, and accountability in financial management. Furthermore, digital systems support data-driven decision-making and strengthen supervisory functions through the availability of systematically documented audit trails. However, the implementation of financial digitalization still faces several challenges, including limited digital literacy among human resources, unequal technological infrastructure, and the need to adapt to new working cultures. Therefore, strengthening human resource competencies, providing adequate technological infrastructure, developing integrated financial information systems, and ensuring continuous policy support are essential factors for the successful transformation of educational financing. The digitalization of financial management has proven to be a strategic instrument for fostering professional, transparent, and accountable financial governance in madrasahs while remaining aligned with the Islamic values of trustworthiness (amanah) in educational management.